PENGUJIAN FRACTAL MARKET HYPOTHESIS (FMH) PADA DINAMIKA RETURN HARIAN NILAI TUKAR DOLLAR AMERIKA SERIKAT (USD) TERHADAP YEN JEPANG (JPY) - Florenta Florenta; Kartono kartono (Jurnal Matematika, 2014)
The concept of Fractal Market Hypothesis (FMH) gives aneconomic and mathematical structure in analyzing the forex market. Fractal has characteristics that are not random, but has a pattern. Fractal experienced recurrence patterns or structures with different scales and sizes, therefore it can show a trend that will occur in the next period.Exchange rate fluctuations cause the trader will have a hard time taking a position of ‘sell’ or ‘buy’. Technical Analysis is the right choice for traders in determining the time to transact. It consists of candlestick analysis in determining the pattern, gradient analysis to determine the level of steepness of exchange rate fluctuations, Rescaled Range analysis (R / S) and the value of Hurst exponent (H) to see characteristics of the return movement, measuring the level of risk (α), measuring the degree of correlation (C) and the fractal dimension (D). In order to complete the final project, the authors do an internship at PT. Futures Monex Investindo Yogyakarta with the data of the exchange rate of United States Dollar (USD) to Japanese Yen (JPY) in the period of January 1, 2005 until December 31, 2013.Based on the results, it can be concluded that the movement of the daily price return of the United States Dollar exchange rate (USD) to Japanese Yen (JPY) result in a system series that is anti-persistent, which means that the series which was up in the previous period, is likely to fall in the next period.